High healthcare resource utilisation due to pertussis in Australian adults aged 65 years and over. Issue 19 (23rd April 2020) - Leong, Robert Neil F.; Wood, James G.; Liu, Bette; McIntyre, Peter B.; Newall, Anthony T.
Abstract: Background: In the context of co-morbid illness and increasing age, data on excess morbidity from pertussis in older adults is crucial for immunisation policy but has been largely limited to case-series. Methods: We designed a matched case-control study nested within a population-based cohort of 267, 153 adults aged ≥45 years in New South Wales, Australia (The 45 and Up Study cohort). Excess hospital bed days, emergency department (ED) admissions, general practitioner (GP) visits, and prescriptions were estimated using negative binomial regression models. An additional self-controlled analysis was also conducted to validate the main models, and to evaluate results for those with either asthma or a body mass index (BMI) ≥ 30 compared to those without these risk factors. Results: Based on 524 pairs of PCR-confirmed pertussis cases and matched controls, we estimated an excess healthcare utilisation per case of 2.5 prescriptions (95% CI: 0.2–4.7), of which 1.1 (95% CI: 0.5–2.2) were antibiotics, 2.3 GP visits (95% CI: 2.0–2.6), and 0.1 ED admissions (95% CI: 0.1–0.2). Compared to those 45–64 years, cases ≥65 years had a significantly greater excess for all prescriptions (1.1 vs 4.7/case), antibiotic prescriptions (0.1 vs 2.2/case), and ED admissions (0.1 vs 0.2/case), but no significant excess of respiratory-related hospital bed days. An additional self-controlled analysis confirmed that cases with either asthma or BMI ≥ 30 had higher overall healthcare utilisation but this was not associated with pertussis infection. Conclusion: We found a substantial excess outpatient healthcare burden among adults aged 65 years and over with PCR-confirmed pertussis, supporting further evaluation of preventive measures.